Analyzing Factors Influencing Supply Chain Management Practices in Medical Device Industry Indonesia - Timotius W. Jefferson; Antonius Siahaan (Conference Series, 2020)
Amidst rapid advancement of technologies; rapid changes of market demands & uncertainties and many competitors in industry, Supply Chain Management has emerged as a leading strategic management tool to create efficiency and effectiveness with the aims to increase organization performance to survive in the market. This study focuses on several organizational capability factors such as Knowledge Management, Organization Agility, and Innovation Capability in relationship with Supply Chain Management Practices. This study uses Structural Equation Modelling (SEM) based on Partial Least Square (PLS) Technique involving 93 respondents whose activities involve supply chain practices in the medical device firms operating in Indonesia. The result of this empirical study shows that those 3 capabilities have significant influence towards the practice of Supply Chain Management.